(untitled) (Damascus University Journal of arts and humanities sciences, 2025)
The research aims to study the relationship between university students’ adaptation problems with courses and low academic achievement. To achieve the research objective, the descriptive analytical approach was used, the social survey method with a sample, and the scale of students’ adaptation problems with courses was used as a research tool, which was prepared by the researcher, and was applied to a random sample of (355) male and female students from the Department of Sociology at Damascus University. After collecting the data, it was analyzed using the (SPSS) program, and a set of results were reached, the most important of which was that the level of adaptation problems with courses among students was average. The results also showed a strong positive correlation between adaptation problems with courses and low academic achievement. The level of adaptation problems with courses among first-year students was higher than in the rest of the academic years. It also showed that there were differences between the adaptation problems of the research sample members with courses according to the gender variable in favor of males. It also showed that students who did not want to specialize were more vulnerable to the problem of poor adaptation to courses. At the end of the research, a set of proposals were presented that could contribute to alleviating this problem and limiting its impact.